Stroke risk factors in an incident population in urban and rural Tanzania: a prospective, community-based, case-control study - Prof. Richard W Walker, MD; Ahmed Jusabani, MD; Eric Aris, MD; William K Gray, PhD; Prof. Nigel Unwin, DM; Mark Swai, MD; Prof. George Alberti, PhD; Ferdinand Mugusi, MD (Elsevier, 2013)
Background: The burden of stroke on health systems in low-income and middle-income countries is increasing. However, high-quality data for modifiable stroke risk factors in sub-Saharan Africa are scarce, with no community-based, case-control studies previously published. We aimed to identify risk factors for stroke in an incident population from rural and urban Tanzania. Methods: Stroke cases from urban Dar-es-Salaam and the rural Hai district were recruited in a wider study of stroke incidence between June 15, 2003, and June 15, 2006. We included cases with first-ever and recurrent stroke. Community-acquired controls recruited from the background census populations of the two study regions were matched with cases for age and sex and were interviewed and assessed. Data relating to medical and social history were recorded and blood samples taken. Findings: We included 200 stroke cases (69 from Dar-es-Salaam and 131 from Hai) and 398 controls (138 from Dar-es-Salaam and 260 from Hai). Risk factors were similar at both sites, with previous cardiac event (odds ratio [OR] 7·39, 95% CI 2·42-22·53; p<0·0001), HIV infection (5·61, 2·41-13·09; p<0·0001), a high ratio of total cholesterol to HDL cholesterol (4·54, 2·49-8·28; p<0·0001), smoking (2·72, 1·49-4·96; p=0·001), and hypertension (2·14, 1·09-4·17; p=0·026) identified as significant independent risk factors for stroke. In Hai, additional risk factors of diabetes (4·04, 1·29-12·64) and low HDL cholesterol (9·84, 4·06-23·84) were also significant. Interpretation: We have identified many of the risk factors for stroke already reported for other world regions. HIV status was an independent risk factor for stroke within an antiretroviral-naive population. Clinicians should be aware of the increased risk of stroke in people with HIV, even in the absence of antiretroviral treatment. Funding: The Wellcome Trust.